2010
DOI: 10.1007/s11270-009-0315-2
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Cu2+ and Cd2+ from Aqueous Solution by Bentonite Clay Modified with Binary Mixture of Goethite and Humic Acid

Abstract: Pre-modification of bentonite clay with goethite, humic acid, and a binary mixture of goethite and humic acid reagents increased its cation exchange capacity from 95 to 105.32, 120.4, and 125.8 meq/ 100 g of bentonite clay, respectively. The effective pre-modification of bentonite clay with goethite, humic acid, and goethite-humic acid reagents was confirmed from their Fourier transform infrared spectra which suggested that modification was effective on the AlAlOH and Si-O sites for goethite and humic acid mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 47 publications
3
21
0
Order By: Relevance
“…It is observed that with the adsorption of metal ions, the peaks at around 3440 and 1030 cm -1 became broad even though there were no significant shifts in these peaks. This indicates an interaction between the metal ions and the modified material (Olu-Owolabi et al 2010). With modification of the kaolinite clay with a binary of goethite and humic acid, cation exchange capacity of the clay increase from 7.81 meq/100 g to 40 meq/100 g while the specific surface area (13 m 2 /g) was the same as that reported by Adebowale et al (2006).…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…It is observed that with the adsorption of metal ions, the peaks at around 3440 and 1030 cm -1 became broad even though there were no significant shifts in these peaks. This indicates an interaction between the metal ions and the modified material (Olu-Owolabi et al 2010). With modification of the kaolinite clay with a binary of goethite and humic acid, cation exchange capacity of the clay increase from 7.81 meq/100 g to 40 meq/100 g while the specific surface area (13 m 2 /g) was the same as that reported by Adebowale et al (2006).…”
Section: Resultssupporting
confidence: 72%
“…After aging, the sample was dried at 50°C, pulverized and sieved through 20-lm sieve. Five percent goethitehumic acid mixture was used for modification based on our previous study (Olu-Owolabi et al 2010). The modified kaolinite produced is now referred to as GHA-modified kaolinite clay adsorbent.…”
Section: Preparation Of Adsorbentmentioning
confidence: 99%
See 1 more Smart Citation
“…The loading of chitosan on bentonite was examined using various reaction times (10-90 min), initial chitosan concentrations (250-2500 mg/L), stirring speeds (50-300 rpm), temperatures (30-50 °C), and pH values (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Specifically, 1 g of raw bentonite clay was dispersed in 150 mL of distilled water.…”
Section: Optimization Of Chitosan Loading Conditionsmentioning
confidence: 99%
“…Meanwhile, bentonite clay remediates some disadvantages of chitosan that affect its adsorption efficacy, e.g. low density, the tendency to float, and difficulty in making contact with pollutants [7,8]. On the other hand, various modification techniques, including acid and thermal (by calcination or microwave radiation) treatments, have been reported to affect the adsorption properties of nature clays for metal ions in aqueous solutions [9][10][11].…”
Section: Introductionmentioning
confidence: 99%